Uncovering Candidate Novel Pluripotency And Cross-Species Complementation Genes By Comparative Transcriptomics In Human And Zebrafish - Goh, Crystal Wei Pin (2015)
Profil transkriptom pluripotensi manusia telah dikenali dengan menggunakan DNA microarray, expressed sequence tag, penjujukan selari besar-besaran, serial analysis of gene expression (SAGE) and SAGE terbalik.